2023
DOI: 10.1136/rmdopen-2023-003350
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of non-pharmacological interventions: a systematic review informing the 2023 EULAR recommendations for the management of fatigue in people with inflammatory rheumatic and musculoskeletal diseases

Eduardo José Ferreira Santos,
Bayram Farisogullari,
Emma Dures
et al.

Abstract: ObjectiveTo identify the best evidence on the efficacy of non-pharmacological interventions in reducing fatigue in people with inflammatory rheumatic and musculoskeletal diseases (I-RMDs) and to summarise their safety in the identified studies to inform European Alliance of Associations for Rheumatology recommendations for the management of fatigue in people with I-RMDs.MethodsSystematic review of randomised controlled trials (RCTs) including adults with I-RMDs conducted according to the Cochrane Handbook. Sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 116 publications
0
11
0
Order By: Relevance
“…Also, exercises have been shown to improve fatigue in other chronic conditions such as RA, HIV, multiple sclerosis, chronic fatigue syndrome, and SLE [ 56 ]. In a recent systematic review, physical activity was found to be effective in reducing fatigue symptoms in a variety of inflammatory rheumatic and musculoskeletal diseases such as RA, SLE, spondyloarthritis, systemic sclerosis and Sjogren’s syndrome [ 19 ]. An examination of the 49 studies encompassed in the review by Hulme et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, exercises have been shown to improve fatigue in other chronic conditions such as RA, HIV, multiple sclerosis, chronic fatigue syndrome, and SLE [ 56 ]. In a recent systematic review, physical activity was found to be effective in reducing fatigue symptoms in a variety of inflammatory rheumatic and musculoskeletal diseases such as RA, SLE, spondyloarthritis, systemic sclerosis and Sjogren’s syndrome [ 19 ]. An examination of the 49 studies encompassed in the review by Hulme et al .…”
Section: Discussionmentioning
confidence: 99%
“…The impact of fatigue may worsen the pre-existing disability in individuals with upper limb and/or lower limb OA. In other rheumatic conditions including RA, SLE, there is strong evidence for the effectiveness of physical activity and psycho-educational interventions in relieving fatigue symptoms [ 19 ]. However, this finding may not be extrapolated to individuals with OA.…”
Section: Introductionmentioning
confidence: 99%
“…The European Alliance of Associations for Rheumatology (EULAR) recently funded a taskforce to examine the effectiveness of non-pharmacological interventions for fatigue in inflammatory rheumatic conditions and the resulting systematic review found strong evidence that some interventions are effective. 14 This informed the EULAR recommendations for the management of fatigue 21 and highlighted a need to better understand contextual factors and the mechanisms by which interventions are effective. 7 There is currently no comprehensive understanding of the factors which influence the success of an intervention.…”
Section: Open Accessmentioning
confidence: 96%
“…A systematic review assessed the quality of evidence available to support non-pharmacological interventions to reduce fatigue in patients with inflammatory rheumatic conditions. 14 The National Institute for Health and Care Research has recently awarded funding for the project 'Effectiveness of Interventions For FatiguE in Long term conditions' (EIFFEL). 18 Study protocols have been registered on the PROSPERO database which state that the team will be conducting two systematic reviews; one to assess the effectiveness of interventions for fatigue in longterm conditions 19 and the other to explore the acceptability of interventions for fatigue.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation